Best linear unbiased estimators for the simple linear regression model using ranked set sampling - Barreto, Maria Cecilia Mendes; Barnett, Vic (Environmental and ecological statistics, 1999)
When sample observations are expensive or difficult to obtain, ranked set sampling is known to be an efficient method for estimating the population mean, and in particular to improve on the sample mean estimator. Using best linear unbiased estimators, this paper considers the simple linear regression model with replicated observations. Use of a form of ranked set sampling is shown to be markedly more efficient for normal data when compared with the traditional simple linear regression estimators.[PUBLICATION ABSTRACT]